2020
DOI: 10.1177/2165079920901534
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, Sleepiness, and Fatigue Among Polish Nurses

Abstract: Background: Sleep disorders can result in sleepiness, fatigue, and apathy, and may contribute to serious occupational consequences such as errors at work. The aim of the study was to examine the level of insomnia, sleepiness, and fatigue in a sample of Polish nurses. Methods: The research was conducted among nurses employed in the Lublin region of Poland. A sample of nurses were invited to participate in a survey in which we measured insomnia, sleepiness, and fatigue using the Athens Insomnia Scale (AIS), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 12 publications
0
24
1
2
Order By: Relevance
“…Sleep disorder can cause drowsiness, fatigue and loss of appetite. On the other hand, this disorder reduces concentration and can cause workplace errors and accidents [ 30 ]. Today, nurses and physicians are at the forefront of the fight against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorder can cause drowsiness, fatigue and loss of appetite. On the other hand, this disorder reduces concentration and can cause workplace errors and accidents [ 30 ]. Today, nurses and physicians are at the forefront of the fight against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the incidence of fatigue is 35.3%-50.00% in the recent relative studies [27,28] . If we do not pay attention to the reasonable arrangement of rest, nurses are prone to fatigue syndrome.…”
Section: Overall Fatigue State Of First-line Nurses In Wuhanmentioning
confidence: 98%
“…Recently, nurses' insomnia has been increasingly studied, but the sample size of existing studies is small and the representativeness is limited. For example, Zdanowicz et al (2020) selected 200 nurses from two hospitals to investigate the current situation of insomnia in Polish nurses, and Wu et al (2020) selected 106 nurses to investigate the sleep quality and its influencing factors of front-line nurses fighting against COVID-19. In addition, most of the existing studies only report the current status, and a comprehensive analysis of the influencing factors of insomnia in nurses is still rare, which makes it difficult to make targeted interventions.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Because of the particularity of their occupation, nurses have a great responsibility, a heavy workload, huge pressure and the need to work in shifts, so they are more likely to suffer from insomnia (Huang, Wu, Ho, & Wang, 2018). The incidence of insomnia among nurses in a certain region of Poland was 47.8% (Zdanowicz, Turowski, Celej‐Szuster, Lorencowicz, & Przychodzka, 2020). In four tertiary hospitals in Shanghai, China, 51.0%–72.1% of nurses in various departments had different degrees of insomnia.…”
Section: Introductionmentioning
confidence: 99%